Soluble Suppression of Tumorigenicity-2 Levels As Prognostic Marker in Non-ST-segment Elevation Myocardial Infarction - Sherly Purnamawaty; Tenri Esa; Ibrahim Abd Samad (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Acute Myocardial Infarction (IMA) is the most severe manifestation of coronary arterial disease, and about 60%-75% ofIMA is NSTEMI. It is known that complications are associated with high mortality rates; therefore, predicting thedevelopment of complications in NSTEMI will help physicians improve risk stratification and determine optimal treatment.Suppression of tumorigenicity-2 (ST2) is a family of interleukin-1 (IL-1) receptors. Ischemia, injury, and myocardial infarctionwill cause cardiomyocytes to release sST2 associated with a worse prognosis. This study aimed to analyze sST2 levels inNSTEMI patients as a prognostic marker. This study used a prospective cohort method performed on NSTEMI patientstreated at Pusat Jantung Terpadu of Dr. Wahidin Sudirohusodo Hospital during March 2019. Forty-two patients wereinvolved as samples. All patients were tested for sST2 levels by immunochromatography and followed up duringhospitalization. Data on the development of heart failure, arrhythmia, cardiogenic shock, sudden cardiac arrest, length ofstay, and outcome were recorded during follow-up. Data were statistically analyzed with Mann-Whitney and Spearman test.The results of the sST2 level in NSTEMI with and without heart failure were 114.09±92.01 ng/mL and 58.94±57.75 ng/mL(p=0.014), respectively. There was no significant difference between sST2 levels in NSTEMI with complications ofarrhythmias, cardiogenic shock, and sudden cardiac arrest compared and patients without those complications (p>0.05).The level of sST2 was significantly higher in NSTEMI patients who passed away (164.05±77.35 ng/mL) than those whosurvived (72.55±73.15 (p=0.027). There was no correlation between sST2 levels and length of stay (p=0.947). It wasconcluded that sST2 levels could be a prognostic marker for NSTEMI, particularly heart failure and outcome.